Effect of Conductive Minerals in the Determination of Water Saturation in “Y” Field - Panduwinata Arifin; Ratnayu Sitaresmi; Benyamin Benyamin (Journal of Earth Energy Science, Engineering, and Technology, 2018)
Formation evaluation is a part of petroleum engineering to study reservoir characteristics as well as issues related to success in the discovery of hydrocarbon reserves. Hydrocarbon reserves are influenced by reservoir rock characteristics consisting of porosity (f), water saturation (Sw), and permeability (k.) In low resistivity regions are often found abnormalities in formation evaluation. The abnormality is a low resistivity value produced so that an inaccurate value obtained when water saturation is calculated. In this study, an evaluation process of the abnormality phenomena was performed on low resistivity areas. The evaluation is done by analyzing both log and core data. Evaluation in low resistivity areas aims to obtain a correction factor of the abnormality that occurs. Abnormalities in the calculation of resistivity values caused by the existence of conductive minerals which resulting in a decrease of the resistivity value of the formation. This correction factor can be used in Archie to calculate water saturations, therefore more accurate values of saturation were found.